Risk and resilience in British Muslim communities. Issue 14 (13th November 2016) - Hargreaves, Julian
ABSTRACT: This article presents findings from a survey of British Muslims communities. It employs the research frameworks of risk, hate crime and grounded theory to examine 'everyday' experiences of victimization and discrimination and the perceived complicity of the British media in creating adverse social conditions for Muslim communities. The article also examines the rather surprising descriptions of agency, personal strength and coping offered by the research participants when discussing their reactions to experiences of hate crime and prejudice. An examination of these reactions was informed by emerging psychological and sociological literatures concerning the concept of resilience.